Transfer of Campylobacter and Salmonella from poultry meat onto poultry preparation surfaces - Sarjit, A.; Dykes, Gary (International Association for Food Protection, 2017)
Copyright © International Association for Food Protection. Thermophilic Campylobacter and Salmonella enterica are major causes of gastrointestinal foodborne infection. Survival of these pathogens on food-associated surfaces is a risk contributing to their spread through the food system. This study examined the transfer of two strains each of C. jejuni, C. coli, Salmonella Enteritidis, and Salmonella Typhimurium from chicken meat to a knife or scissors used on either a plastic or wooden cutting board. Each strain of Campylobacter and Salmonella at ~10 8 CFU mL 1 was inoculated (5 mL) onto 25 g of chicken meat with skin and allowed to attach (for 10 min). The meat was then cut (20 times per implement) into 1-cm 2 pieces with either a knife or scissors on either a plastic or wooden cutting board. The numbers of pathogens transferred from meat onto cutting implements and cutting board surfaces were enumerated. The surfaces were subsequently either rinsed with water or rinsed with water and wiped with a kitchen towel to mimic commonly used superficial cleaning practices for these implements, and the numbers of pathogens were enumerated again. The bacterial numbers for both pathogens were determined on thin-layer agar. The attachment of the Salmonella strains to chicken meat (~7.0 to 7.8 log CFU cm -2 ) was higher than the attachment of the Campylobacter strains (~4.6 to 6.6 log CFU cm -2 ). All four Salmonella strains transferred in higher numbers (~1.9 to 6.3 log CFU cm -2 ) to all surfaces than did the Campylobacter strains (~1.1 to 3.9 log CFU cm -2 ). The transfer rates of both pathogens from the chicken meat to all the surfaces examined varied substantially between ~0 and 21.1%. The highest rate of transfer (~21.1%) observed was for C. coli 2875 when transferred from the chicken meat to the scissors. Most cleaning treatments reduced the numbers of both pathogens (~0.3 to 4.1 log CFU cm -2 ) transferred to all the surfaces. Our study gives insights into the risks associated with the transfer of Campylobacter and Salmonella from poultry to the surfaces used in poultry preparation.